Lymphovascular invasion, race, and the 21-gene recurrence score in early estrogen receptor-positive breast cancer - Della Makower (Nature Portfolio, 2021)
Abstract Lymphovascular invasion (LVI) and Black race are associated with poorer prognosis in early breast cancer (EBC). We evaluated the association between LVI and race, and whether LVI adds prognostic benefit to the 21-gene recurrence score (RS) in EBC. Women with ER+ HER2− EBC measuring up to 5 cm, with 0–3 involved axillary nodes, diagnosed between 1 January 2010 and 1 January 2014, who underwent surgery as first treatment and had available RS, were identified in the NCDB database. Bivariate associations between two categorical variables were examined using chi-square test. Multivariate Cox proportional hazards model were used to assess the association of LVI, race, and other covariates with overall survival (OS). 77,425 women, 65,018 node-negative (N0), and 12,407 with 1–3 positive (N+) nodes, were included. LVI was present in 12.7%, and associated with poor grade, RS 26–100, and N+ (all p < 0.0001), but not Black race. In multivariate analysis, LVI was associated with worse OS in N0 [HR 1.37 (95% CI 1.27, 1.57], but not N+ EBC. LVI was associated with worse OS in N0 patients with RS 11–25 [HR 1.31 (95% CI 1.09, 1.57)] and ≥26 [HR 1.58 (95% CI 1.30, 1.93)], but not RS 0–10. No interaction between LVI and chemotherapy benefit was seen. Black race was associated with worse OS in N0 (HR 1.21, p = 0.009) and N+ (HR 1.37, p = 0.015) disease. LVI adds prognostic information in ER+, HER2−, N0 BCA with RS 11–100, but does not predict chemotherapy benefit. Black race is associated with worse OS, but not LVI.